2022
DOI: 10.1002/bdm.2295
|View full text |Cite
|
Sign up to set email alerts
|

Mementos and the endowment effect

Abstract: This research provides evidence for a new moderator of the endowment effect: having a memento of the endowed object. Three studies adapting classic endowment effect paradigms and using a variety of endowment objects and mementos demonstrate that having a memento of an endowment increases willingness to trade the endowment and decreases selling prices for the endowment. We provide evidence that mementos attenuate the endowment effect regardless of whether the memento is a separate small gain when facing the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The hypothetical test further showed if willingness to accept was significantly higher than willingness to pay. Endowment was defined as a scenario where the willingness to accept is significantly higher than the willingness to pay (Chu & Shu, 2023;Morewedge & Giblin, 2015;Smitizsky et al, 2021). Rejecting the null hypothesis implies that there is a significant difference between buyers' and sellers' valuations and willingness to accept is significantly higher than willingness to pay, concluding that the endowment effect is present in the housing market.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothetical test further showed if willingness to accept was significantly higher than willingness to pay. Endowment was defined as a scenario where the willingness to accept is significantly higher than the willingness to pay (Chu & Shu, 2023;Morewedge & Giblin, 2015;Smitizsky et al, 2021). Rejecting the null hypothesis implies that there is a significant difference between buyers' and sellers' valuations and willingness to accept is significantly higher than willingness to pay, concluding that the endowment effect is present in the housing market.…”
Section: Methodsmentioning
confidence: 99%
“…The concept was further explored by Knetsch and Sinden (1984), who defined it as a state in which the willingness to accept significantly exceeds the willingness to pay for an identical commodity. As of then, the existence of the WTA and WTP gap has sparked a lot of debate in different fields of study, such as the retail sector (Wang, 2009), business investment decisions (Peñón & Ortega, 2018), politics (Alesina et al, 2015), management (Harcourt et al, 2020;Ştir & Zaiţ, 2022), social psychology (Chu & Shu, 2023;Smitizsky et al, 2021;Yamamoto & Navarro-Martinez, 2022), environment (Dietz & Venmans, 2019;Villanueva & Gómez-Limón, 2023) and the real estate sector (Gong et al, 2019;He & Asami, 2014;Paraschiv & Chenavaz, 2011;Yan et al, 2021). The application of the endowment effect to the real estate sector got the attention of scholars due to valuation inconsistencies, where buyers and sellers do not value properties to the same market price (Gong et al, 2019;Paraschiv & Chenavaz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chu and Shu [8] summarize that the endowment effect clarifies a tendency for individuals to demand more for selling an object they possess than the price people give up for the preliminary purchase of this object. Mi [5] points out that because of the loss aversion psychology, people have the inclination to put a premium when selling their possessions.…”
Section: Endowment Effectmentioning
confidence: 99%
“…Second, the literature on psychological ownership has found that extending ownership beyond simple legal ownership of the object onto a memento or reminder of the object (e.g., by taking a photo of the good) may increase the seller's willingness to dispose of goods they care about (Chu 2018;Chu and Shu 2022;Kellett and Holden 2014;Winterich, Reczek, and Irwin 2017). Since heritage goods connect individuals to a shared past, their psychological ownership is, at least in part, collective (Belk 2010(Belk , 2017Curasi, Price, and Arnould 2004;Epp and Price 2008;Lastovicka and Fernandez 2005;McCracken 1986).…”
Section: Theoretical Developmentmentioning
confidence: 99%